PENERAPAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA KELAS IV SDN 166 TANGRU KABUPATEN ENREKANG - Nur Afni; Abdul Malik Iskandar; Cayati; Nurhadifah Amaliyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Nur Afni, 2025. Implementation of the Time Token Learning Model to Improve Science Learning Motivation of Fourth-Grade Students at SDN 166 Tangru. Thesis. Faculty of Teacher Training and Education, Mega Rezky University, (supervised by: Abdul Malik Iskandar and Cayati) This study aims to improve student learning motivation through the application of the Time Token Learning Model to improve fourth-grade students at SDN 166 Tangru. To achieve this goal, the approach used in this study is Classroom Action Research (CAR). Data collection was conducted through observation, questionnaires, and documentation, while data analysis was conducted using techniques including data reduction, data presentation, and conclusion drawing. The results of this study indicate that teacher activities during learning using the Time Token Learning Model to improve student learning motivation experienced significant improvements from Cycle I to Cycle II. The results of observations of student learning motivation increased to 27.78% in Cycle I, meeting one, and then increased again to 55.56% in Cycle I, meeting two. In the first meeting of cycle II, 72.22% of students were able to meet all the learning motivation indicator criteria. In the second meeting of cycle II, 88.89% of students met all the learning motivation indicator criteria. Based on these research results, it can be concluded that the students' motivation to learn science at SDN 166 Tangru has increased. Therefore, the time token learning model can be considered an effective and efficient learning model for increasing student learning motivation. Keywords: Time Token Learning Model, Learning Motivation